Stratigraphy of organic-rich deposits in floodplain environments: examples from the upper Odra river basin - Wójcicki, Krzysztof J. (Quaestiones Geographicae, 2012)
Macrofossil analysis and radiocarbon dating were used to determine the age, composition and succession pattern of organic-rich deposits infilling oxbows and flood basins in the Rivers Kłodnica, Odra and Osobłoga valleys (southern Poland). Both detrital sediments representing the aquatic or terrestrial environments as well as five types of peat accumulated in amphibious or peatland conditions have been identified in cores analyzed. Studies have shown that an accumulation of organic-rich deposits was commonly initiated by terrestrialisation and was typically occurred under eutrophic conditions. In such circumstances, deposit sequences usually begin with aquatic detrital sediment (gyttja), or possibly brown-moss or reed peat. These deposits normally pass into sedge-reed peat and then alder peat. If the accumulation of organic-rich deposits was initiated by paludification, alder peat appears in the lowest sections of the fens. In the upper parts of the sequences, apart from wood peat, organic deposits dominated by sedge remains are also present. The latter were accumulated, probably, as an indirect effect of human activities in the floodplains.